Effect of pulsed field ablation on solid tumor cells and microenvironment - Wang, Yujue; Jiang, Tian’an; Xie, Liting; Wang, Huiyang; Zhao, Jing; Xu, Lei; Fang, Chengyu (Frontiers in Oncology, 2022)
Pulsed field ablation can increase membrane permeability and is an emerging non-thermal ablation. While ablating tumor tissues, electrical pulses not only act on the membrane structure of cells to cause irreversible electroporation, but also convert tumors into an immune active state, increase the permeability of microvessels, inhibit the proliferation of pathological blood vessels, and soften the extracellular matrix thereby inhibiting infiltrative tumor growth. Electrical pulses can alter the tumor microenvironment, making the inhibitory effect on the tumor not limited to short-term killing, but mobilizing the collective immune system to inhibit tumor growth and invasion together.